Conservation of Biological Diversity in the Garhwal Himalayas - Rawat, J. K.; Sharma, S. K. (Indian Forester, 1992)
Biological diversity in the Garhwal Himalaya has been described highlighting the endangered species of flora and fauna there. Various conservation efforts in progress in the region, grouped under (i) habitat and species protection, (ii) legislation and (iii) public awareness and voluntary agenCies, have been reported. Some suggestions for promoting biodiversity conservation have also been put forward.